π-Conjugated fluorenyl-based phthalocyanines: Synthesis, photophysical, photochemical properties, and biological evaluation - Sajjadifard, Bahareh; Karaoglu, Hande Pekbelgin; Karanlik, Ceren Can; Erdogmus, Ali; Yalcin, M. Serkan; Ozdemir, Sadin; Burat, Ayfer Kalkan (ELSEVIER SCI LTD, 2026)
In the current study, a new phthalonitrile derivative, 4-((9,9-bis(5-hydroxypentyl)-9H-fluoren-2-yl)ethynyl) phthalonitrile (4), was successfully synthesized. Fluorene units were introduced to improve solubility, expand It-conjugation, and tailor photophysical and photochemical properties relevant to PDT and biological applications. Dialkyl-substituted fluorene groups were incorporated into peripherally tetra-substituted zinc (ZnPc) and indium (InPc) phthalocyanines via an acetylene bridge. The fluorescence characteristics and singlet oxygen generation abilities of zinc (5) and indium phthalocyanines (6) were thoroughly examined. To the best of our knowledge, this is the first study to investigate the biological properties of bis(hydroxypentyl)-substituted fluorene-based phthalocyanines across multiple biological parameters. Both, ZnPc (5) and InPc (6) exhibited notable antioxidant, antidiabetic, and DNA cleavage activities. In antimicrobial tests, Enterococcus faecalis, Enterococcus hirae were found to be the most sensitive microorganisms for both compounds, with minimum inhibitory concentrations (MICs) of 8 mg/L. The antibiofilm activities of ZnPc (5) against Pseudomonas aeruginosa and Staphylococcus aureus were 73.1 % and 79.2 %, respectively, while those of InPc (6) were 65.1 % and 68.9 %, respectively. Additionally, ZnPc (5) and InPc (6) showed a concentration-dependent increase in the inhibition of Escherichia coli cell viability, reaching 89.9 % and 97.5 % at 15 mg/L, respectively. In the tests, an increase in antimicrobial and antibiofilm activities was observed under photodynamic antimicrobial therapy (PADT). The most effective MIC value (2 mg/L) was obtained against Enterococcus hirae under PADT conditions. Upon light irradiation, the antibiofilm inhibition rates of ZnPc (5) increased to 94.7 % for Pseudomonas aeruginosa and 91.6 % for Staphylococcus aureus, while InPc (6) exhibited 86.1 % and 86.2 % inhibition against the same pathogens. These results highlight the promising potential of ZnPc (5) and InPc (6) for biomedical applications, particularly in photodynamic therapy and antimicrobial treatments.
Keywords: Synthesis; Photophysical; Photochemical; Biological; Phthalocyanine; PHOTODYNAMIC THERAPY; ZINC-PHTHALOCYANINE; DERIVATIVES; SUBSTITUENTS; INACTIVATION; BLUE; RED; Chemistry; Engineering; Materials Science